Laboratory Liquid Waste Processing Effots Using Pineapple Skin Extract (Ananas Comosus (L) Merr.) To reduce Cuprum (Cu) Concentration - Sabata, Lice; Handayani, Oktia Woro Kasmini; Pawenang, Eram Tunggul (Universitas Negeri Semarang, 2025)
The Waste from chemistry practical activities is classified as Hazardous and Toxic Materials (B3). B3 waste must undergo processing because it can seep into the soil and potentially damage groundwater quality and health risks to the public. High levels of Copper (Cu) are toxic and accumulate in vital organs, affecting human health. The importance of wastewater treatment efforts in laboratories. Utilizing Cayenne pineapple peels as a waste treatment medium has economic value. Cayenne pineapple skin is high in potassium and acids, which can precipitate Cu. The aim of the research is to reduce the concentration of Cu in liquid waste using pineapple peel extract. Methods: Experimental research with Cuprum parameters using spectrophotometry and Total Plate Count (TPC). Results: Pineapple peel extract is capable of reducing copper levels (sig. 0,047;BF 44,75), meaning there is a difference in the addition of pineapple peel extract with copper levels. Extract 10% pineapple peel (30%). Extract 20% pineapple peel (5%-48%). Extract 30% pineapple peel (6%-29%). Extract 40% pineapple peel (74%). The addition of a 50% pineapple peel (20%-71%). The results of the pineapple skin extract's effect on the reduction of germ counts show a not significant difference in the laboratory wastewater samples.